Characteristic absorption band split of symmetrically tetra-octyloxy metal phthalocyanines. (September 2015) - Cong, Fangdi; Wei, Zhen; Huang, Zhiqiang; Yu, Fengyang; Liu, Haixue; Cui, Jing; Yu, Helong; Chu, Xinxin; Du, Xiguang; Xing, Kezhi; Lai, Jianhong
Abstract: An interesting phenomenon was that some symmetrically substituted metal phthalocyanines behaved characteristic absorption band split in non-coordinated solvents especially when they had zinc as the center metal and alkyloxy substituted groups at non-periphery of molecular skeleton, for example tetra- α -octyloxy zinc phthalocyanine having split peaks at 706 and 752 nm in chloroform, respectively. The red split peak at 752 nm could be strengthened by acid enhancing macromolecular conjugation, and contrarily weakened by alkali. Further a linear relationship was found between the relatively alteration value of characteristic absorbance and the concentration logarithm of acid in chloroform from 1.18 × 10 −5 to 1.39 × 10 −1  mol/L, which implied its potential application in analysis on trace of total acids included in grain, food and medicine, etc. Graphical abstract: Highlights: Symmetrically substituted metal phthalocyanines behave Q band split. The split requires zinc, α-substituted position and non-coordinated solvent. The split peaks could be tuned by acid and alkali as well as solvents. The altered Q absorbance is linear with the concentration logarithm of acid.